Central banks' predictability: An assessment by financial market participants - Bernd Hayo; Matthias Neuenkirch (Philipps-University Marburg, School of Business and Economics, 2016)
In this paper, we examine the relationship between market participants' perception of central bank predictability and their assessment of central bank communication skills and success in conveying objectives as well as the importance of transparencyenhancing measures, such as voting records, transcripts or minutes of policy meetings, and conditional interest rate projections. Our analysis is based on a unique dataset of almost 500 market participants worldwide who were asked questions with respect to the performance of the Bank of England, the Bank of Japan, the European Central Bank, and the Federal Reserve. Our results indicate a positive and economically notable relationship between central banks' ability to convey their objectives and their overall communication skills on the one hand, and market participants' perception of the banks' predictability on the other hand, for all four central banks. The dissemination of more specific information does not appear to contribute to better central bank predictability. This raises doubts about the widely-held notion that implementing ever more transparency-enhancing measures will improve central bank predictability.
Keywords: E52; E58; 330; Central Bank; Communication; Financial Market Participants; Objectives; Predictability; Survey; Transparency